(untitled) (Canadian Rheumatology Today, 2024)
Lupus Nephritis (LN) is a common and severe manifestation of systemic lupus erythematosus (SLE), impacting up to 40% of SLE patients. Despite advancements in understanding the pathogenesis of LN, outcomes have not significantly improved since the early 2000s. LN patients face higher mortality, emphasizing the importance of achieving disease remission. Screening for nephritis involves regular monitoring, especially within the first 5 years of SLE diagnosis. Monitoring includes urinalysis, serum creatinine, and immune serology. Kidney biopsy remains the gold standard for LN diagnosis and classification, providing crucial information for treatment decisions. The standard of care involves hydroxychloroquine for all LN patients, with immunosuppressive treatments tailored to the histologic class. The recently approved medications, belimumab and voclosporin, offer additional therapeutic alternatives. Approximately 20% of LN patients exhibit features of thrombotic microangiopathy, warranting anticoagulation. Optimizing glucocorticoid dosing is recommended, favouring lower doses to minimize adverse effects. Lifelong monitoring is essential, as flares can occur at any point, emphasizing the need for continued immunosuppression. Given the lack of renal response in 30–60% of patients, the addition of combination therapies, such as calcineurin inhibitors or belimumab, should be considered. Duration of treatment is crucial, considering the progressive loss of podocytes and nephron function, which may lead to chronic kidney disease. Regular monitoring, maintenance immunosuppression, and lifestyle modifications contribute to preventing flares and improving long-term outcomes for LN patients.